The March of the Ukrainian Rebels to the Baltic Countries - Vjatrovič, Volodymyr (Genocidas ir rezistencija, 2006)
In 1950 but five years had passed since the last shots of the Second World War had echoed throughout Europe. For the Soviet Union the World War II ended not only in the victory against Germany, but also in the acquisition of a broad zone of influence in Eastern and Central Europe. It seemed that the USSR had reached the peak of its power and that there was no counterweight to it. Nevertheless, there were in fact anti-Soviet outbreaks in all the western periphery of the empire, in the lands occupied already on the eve of WWII. Particularly strong resistance developed in West Ukraine and Lithuania. The leadership of the Ukrainian liberation movement recognised the nations suppressed by Soviet imperialism as their strategic allies. Having formed an alliance with these nations, the Ukrainians sought to subvert the existing imperialist regime and to establish a new international system based on the principle of self-determination of nations. The fight organised in order to implement the slogan raised by the Ukrainian revolutionaries, "Freedom for the nations! Freedom for the individual!" had to become the core of cooperation of the anti-Communist movements. Aiming for this, the troops of the Ukrainian rebel army (Ukrainska povstancha armija, UPA) organised propaganda campaigns in Belarus, Poland, Czechoslovakia, and Romania. The usual methods of propaganda, such as the spread of proclamations or other type of underground literature among the citizens of the other countries, were not sufficient in this particular case. It was because the citizens of these counties either did not hear anything about the Ukrainians rebels, or would hear only what was provided by the propaganda against the Ukrainian liberation movement. In such conditions the propaganda effect had to be strengthened by the participation of the Ukrainian rebels. In 1945–1947, the Ukrainian rebels launched a number of successful marches on the territory of Poland. As a result, Polish citizens not only changed their opinion about the UPA in a positive way, but also increased cooperation with the Polish underground began. They even succeeded in organising a few operations in common. Particularly successful were the UPA campaigns in Slovakia; they resulted in increased activities of the local anti-Communist movements which actually had an impact on the elections to the Parliament of the Republic of Czechoslovakia in 1946. A huge achievement of those propaganda campaigns was the fact that the major newspapers in Europe and America wrote about the Ukrainians rebels. Yet, very soon, in the second half of 1947, after the Ukrainian underground activities had been terminated in Zakerzonia (the et huic lauds of the Ukrainians annexed to Poland after 1945), the Ukrainian liberation movement in fact lost its chance to effect on the events in the Central and Eastern Europe. Nevertheless, the Ukrainian rebels continued to break the information blockade. In the summer of 1949, they organised a successful march of the rebel troops to Romania. After this campaign on 3 September 1949, the Chief Command of the UPA ordered the release of the Ukrainian rebel army, and urged their soldiers to join the ranks of the armed underground of the Ukrainian Nationalist Organisation (Organizacija ukrainskich nacionalistov, OUN). Yet, even then, the Ukrainian underground attempted to organise one more march abroad, this time to the Baltic countries. The aim of this campaign was the same as the others – to spread among the Baltic peoples the ideas of the Ukrainian liberation movement and to reach out to the local underground. The resist once movements of the Baltic countries and the Ukrainian movement that were the strongest anti-Soviet forces at that time. The rebel march to the Baltics is a not well known. None of those who took part left any memoirs; we have only the proclamations prepared for dissemination during that march. For a long time it was actually unclear whether this action had been implemented at all, or whether it remained but a plan of the Ukrainian underground. The first to relate the march to the Baltic countries was Marija Savchina, the wife of one of the organisers of the march, also Vasilij Galasa, in her memoirs, "A Thousand roads". Later, V. Galasa himself reflected on this action in more detail in his own memoirs. He arranged special orders to the campaign’s participants and wrote the proclamations. Since the march was to cross Belarus, along with the proclamations to the nations of the Baltic countries "Lithuanians, Latvians, Estonians!" (in the Ukrainian language, and also a shortened version in Russian) there was another proclamation "To the people of Belarus". The appeal to the nations of the Baltic countries mainly highlighted the necessity for close cooperation among the liberation movements of all suppressed nations. V. Galasa wrote, "Lithuanians, Latvians, Estonians! Our nations have to fight for their liberation together and the only sound solution is the fight aimed to establish independent national states of all the nations suppressed by Moscow... Revolutionaries of Lithuania, Latvia, and Estonia! Strengthen your cooperation with our liberation movement. Send to Ukraine your underground publications, proclamations and appeals. Encourage your fellow-countrymen who are serving in the enemy’s army, deported to forced labour in Siberia, confined in prisons and concentration camps and in all other circumstances to establish friendly connections and together assist the fight against the occupiers. We have been doing this before, are doing so now, and will be doing so in the future". A group of twelve rebels, under the command of the Kashyr Kamen region leader Rybak, was formed for the march. They started the march at the end of August 1950. The route led through the settlements of the Belarusian regions of Drogichiu, Beloozersk, Ruzhau, Slonim and Baranovich. The first days of the march were rather easy for the rebels, as they had been in the Belarusian border regions before, knew them well, and had many acquaintances there. We read in the memoirs of V. Galasa, "the rebels organised several meetings with the Belarussian teachers and gave them some of our literature. During our conversations, the teachers listened to us silently, not revealing their opinions. They would respond to our questions with caution; maybe because they were afraid of the MGB, or maybe because of their beliefs." After a few days of the propaganda campaign of the Ukrainian rebels, information about their presence in Belarus reached the local authorities, including the Soviet security forces. "In a few days after our visits to the Belarussian villages, the units of the BSSR MVD army began blocking the roads, bridges, and river crossings. Operational troops and secret agents were sent to the forests; roadblocks were set. By all appearances, the enemy understood we were heading to Lithuania, and blocked the forests in that direction." It became impossible to move in the direction apparently known to the enemy, on the territory they controlled. Thus, the group failed to reach Lithuania, and had to return to Volyn. Yet, Soviet forces did not intend to let the rebels alone. When, on their way back, the Ukrainian propagandists were crossing the Yaselda River in the Beloozersk region, the Soviets organised a roadblock. The rebels managed to escape without losses and succeeded in reaching their homeland. It is very probable that the march had been planned as the start of a larger campaign to reach out to the underground in the Baltics. It is likely that after the first group failed, the order to send other groups was cancelled and the implementation future actions was postponed. This was the last attempt of the Ukrainian rebels to organise a foreign campaign. Moscow was sure that the underground struggle was over. Nevertheless, the Ukrainian rebels had resolved to make a brave move; they made efforts to affiliate with the brothers-in-arms from the Baltic countries. Despite this failure, the effort proved the ideological power of the Ukrainian underground. Even after great losses the underground aimed to implement their strategic goal – to subvert Soviet imperialism with the forces of the conquered nations.